Sharenting, Peer Influence, and Privacy Concerns: A Study on the Instagram-Sharing Behaviors of Parents in the United Kingdom - Ranzini, Giulia; Newlands, Gemma; Lutz, Christoph (Social media + society, 2020)
Parental sharing of child-related content on social network sites, termed “sharenting,” is often the target of criticism. Yet, through sharenting, parents can find support systems, a way to stay in touch with relevant others, and even an opportunity for additional income. This study contributes to knowledge on antecedents of sharenting. It explores the impact of parents’ privacy concerns on the sharing of child-related content, as well as on their general Instagram sharing. In this study, we differentiate between general and situational privacy. Moreover, we investigate whether parents’ privacy self-efficacy and the support of their peers influence parental sharing practices. Drawing on a rich body of literature on privacy and information sharing, we discuss the results of an online survey distributed among 320 Instagram users who are parents of children younger than 13 and reside in the United Kingdom. We find that parents’ privacy concerns are uncorrelated to sharenting and only situational concerns marginally correlate to parents’ general sharing. Parents’ reported privacy self-efficacy also did not play a role in parents’ sharing of either personal or children-related content. On the contrary, both Instagram sharing and having a network supportive of parental sharenting positively predict sharenting. Our results indicate that (a) neither situational nor general privacy concerns influence parents’ sharenting behavior, and (b) a parent’s supportive network and frequent sharing habits make frequent sharenting more likely.